The impact of warehouse receipt system on income poverty reduction of cashewnut farmers in Newala District - Mpita, Halima Ajali (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for the award of Degree of Master of Science in Economics (MSc. ECO) of Mzumbe University